Effects of advanced maternal age on pregnancy outcome - Rajput, Neelam; Paldiya, Deepak; Verma, Yogendra S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Advanced maternal age, generally signify age after 35 years at the time of delivery. It is associated with decreased fertility and increased risk. Methods: This was a prospective study conducted in Kamla Raja Hospital, G.R. Medical College, Gwalior (M.P.) during the period of one year from July 2015 to June 2016. Pregnant women aged 35 years and older at the time of delivery were selected and analyzed for maternal and perinatal outcome. Results: A total no. of 288 elderly pregnant patients were selected for the study. Most of the cases were in the age group 35 to 39 years (89.93%). Multi gravida (71.8%) and grand multi para (22.22%) constituted the largest group. Most of the cases belong to lower socio-economic status (90%). Percentage of unbooked cases was 82.98%. The causes of delay in pregnancy were preference for male child (23.95%) and unwareness of contraception (21.52%). The incidence of diabetes mellitus and chronic hypertension were increased. Overall cesarean rate was increased (35%). Incidence of abortions 28(9.72%), preterm delivery 18(6.25%), oligohydramnios 18(6.25%), APH 18(6.25%) and PROM 17(5.90%), low birth weight baby 30(13.19%), NICU admission 20 (6.94%), IUGR 11(3.81%) all were high. The preference for male child 69(23.95%) and lack of awareness 62(21.52%) were two major reason for continuing pregnancies and deliveries till late age. Conclusions: The present study showed that pregnancy at advanced age is a higher risk pregnancy in term of increased maternal and perinatal morbidity and mortality.